Tourism : principles and practice - Fletcher, John (John Edward), ....-; Fyall, Alan, ....-; Gilbert, David, ....- (Harlow : Pearson, 2018)
Thanks to its engaging writing style and accessible structure, Fletcher has become the ultimate one-stop text for any student studying Tourism. Its broad appeal and popularity increases with each new edition, making it excellent value for any student who wants to understand and explore the principles of the subject. Well-liked by students and lecturers alike, Tourism: Principles and Practice is the ultimate reference text for anyone wishing to understand the complex and varied issues involved with such a diverse and constantly changing subject.
Keywords: Tourism -- HOWEST